Pemanfaatan electronic Word of Mouth Communication (eWOM) Guna Pengembangan Wisata Kecamatan Modung Kabupaten Bangkalan - Conny Dian Sumadi; Tyasmiarni Citrawati (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2022)
Electronic word of mouth communication that is formed on social media allows users to share information with each other through comments or reviews about certain tourist destinations, this is able to attracct other users to come to visit. To promote Modung as a tourist village destination, a strategy is needed. One of them is the electric Word of Mouth (eWOM) tecnique. In relation to the world of tourism, purchasing decisions are assumed to e visiting decisions so that theories regarding purchasing decisions are also used in visiting decisions. Additionally, in commercial situations WoM involves customers sharing attitudes, opinions or reactions about a busniess, product or service with others. Positive WoM is also considered as a strong market communication medium for companies to influence customers, especially to visit the tourism village.